2023
DOI: 10.1038/s41467-023-40977-5
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal rhythms of wrist temperature are associated with future disease risk in the UK Biobank

Thomas G. Brooks,
Nicholas F. Lahens,
Gregory R. Grant
et al.

Abstract: Many chronic disease symptomatologies involve desynchronized sleep-wake cycles, indicative of disrupted biorhythms. This can be interrogated using body temperature rhythms, which have circadian as well as sleep-wake behavior/environmental evoked components. Here, we investigated the association of wrist temperature amplitudes with a future onset of disease in the UK Biobank one year after actigraphy. Among 425 disease conditions (range n = 200-6728) compared to controls (range n = 62,107-91,134), a total of 73… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Disruptions in circadian rhythms are associated with a higher risk of cardiovascular diseases, ischemic heart disease, and mortality [ 42 , 43 ]. It has been shown that decreased body temperature might serve as a predictor of cardiovascular complications [ 28 ], while alterations in body temperature rhythm amplitude are inversely related to longevity: reduced amplitude correlates with increased mortality [ 44 ], whereas increased amplitude is linked to longer life expectancy [ 45 ]. In this context, Tcore fluctuations might serve as a biomarker for developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in circadian rhythms are associated with a higher risk of cardiovascular diseases, ischemic heart disease, and mortality [ 42 , 43 ]. It has been shown that decreased body temperature might serve as a predictor of cardiovascular complications [ 28 ], while alterations in body temperature rhythm amplitude are inversely related to longevity: reduced amplitude correlates with increased mortality [ 44 ], whereas increased amplitude is linked to longer life expectancy [ 45 ]. In this context, Tcore fluctuations might serve as a biomarker for developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…As a gauge of peripheral thermoregulation, wrist temperature, which can be assessed by monitoring, is a promising digital biomarker for numerous diseases [86]. The relationship between the circadian rhythm of temperature and metabolic features is well known for mammalian species and humans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, any periodic fluctuation in core body temperature observed in daily life may be caused by diet-induced thermogenesis or physical activity, leading to an increase in core body temperature during the active phase when food intake occurs and a decrease during the resting phase. In the context of distal skin temperature rhythmicity, the peak-to-trough difference of the endogenous circadian rhythm, measured in highly controlled conditions, is about 3.5°C, while this is 6°C in freely living conditions, likely conditioned by behavioral and environmental components [ 22 ]. In clinical settings, medical activities such as drug administration, mechanical ventilation, nutritional support, or physical therapy as well as excess sound and artificial light may impose daily rhythms on physiology or completely mask or abolish them.…”
Section: Daily Rhythms In Physiologymentioning
confidence: 99%
“…Wearable technology for longitudinal recording of physiological or behavioral variables is extensively adopted in the field of chronobiology to characterize 24-hour patterns in variables of interest. Some examples include activity trackers [ 74 , 75 ], continuous glucose monitoring [ 76 ], wrist temperature [ 22 ], and heart rate [ 76 , 77 ]. The relevance of using wearables for circadian monitoring in patient populations is exemplified by studies showing the predictive value of circadian metrics and clinical outcomes in patient populations, such as circadian features of heart rate as a prognostic marker for postoperative recovery scores [ 78 ] and rest–activity cycles as a predictor for patient survival [ 79 ] in oncology patients.…”
Section: Opportunities For the Use Of Ehr In Circadian Medicinementioning
confidence: 99%